Taste and the tomato in Italy: a transatlantic history - Gentilcore, David (Food & History, 2009)
Abstract The experience of the arrival, reception and success of New World products in Europe – tomatoes, maize, potatoes, chillies, etc. – is a unique event in the culinary history of the continent. The assimilation of each foodstuff has its own distinct trajectory. This article explores how the tomato gradually and slowly came to dominate Italian cookery and food exports, after inauspicious beginnings in the 1500s, by following the tomato’s itinerary, back and forth across the Atlantic. We do this through the medium of “taste”, analysing the role it had to play in shaping the different stages of the tomato’s Italian history.